Influence Service Quality on Customer Satisfaction on MDP IT Superstore - Arfianti, Nabila Anggi; Megawati, Megawati (Sean Institute, 2025)
This research aims to examine the influence of service quality on customer satisfaction at Mdp It Superstore. This research uses a quantitative method carried out by customers who have made more than one purchase at MDP IT Superstore. The data analysis method uses non-probability sampling, purposive sampling, and multiple regression with a sample of 400 respondents. Based on the results of the partial test (t test) it shows that the Service Quality has a positive and significant influence on Customer Satisfaction. The research results simultaneously have a significant effect on customer satisfaction.